(untitled) (Research, Society and Development, 2020)
The objective of the research was to analyze the knowledge of undergraduate nursing students about screening and early diagnosis of cervical cancer. This was a cross-sectional study, with a quantitative approach, carried out with 112 students from a public institution of higher education in Paraíba. The instrument used was a structured questionnaire. For the bivariate analysis, the Epi Info 7.2.2.2 software was used, Pearson’s chi square and Fisher’s exact tests were applied. It was observed that students who were in group 2, those who had the opportunity to provide assistance to women and those who participated in some extracurricular activity demonstrated greater knowledge about the subject investigated. The participants had more expressive knowledge about screening than about early diagnosis. The study indicates the need for investment in the training process of nurses to expand and qualify knowledge about cervical cancer.